2010
DOI: 10.1111/j.1365-2702.2009.03133.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Investing in the future’: residential aged care staff experiences of working with nursing students in a ‘community of practice’

Abstract: In a 'communities of practice' model of clinical experience for students, there are benefits for staff as well as students. The implementation of this clinical model in residential aged care was relatively low in cost, a benefit in this sector and has the potential to address the critical issues of recruitment and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 29 publications
(51 reference statements)
3
79
0
Order By: Relevance
“…There are also benefits to staff in exchanging knowledge and new techniques with students and being involved in an interdisciplinary model of care that has had a positive impact and has been incorporated in how they deliver care. Staff spoke of their increased motivation that results in helping students to learn and this is also acknowledged in the literature (Grealish et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also benefits to staff in exchanging knowledge and new techniques with students and being involved in an interdisciplinary model of care that has had a positive impact and has been incorporated in how they deliver care. Staff spoke of their increased motivation that results in helping students to learn and this is also acknowledged in the literature (Grealish et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted among university graduates in health professions have indicated that many do not consider working in residential aged care within a community as a viable career option (Abbey et al 2006). Furthermore, many regard it as a limiting and an uninteresting career option (Grealish et al 2010). For example, a study conducted by Moyle (2003) showed that nursing graduates rank a career in aged care lower than any other field.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it seemed that formalized strategies or educational models were needed to enhance the students' learning experiences. Other studies have emphasized the need for close collaboration between placement arenas and educational institutions (Campbell and Jeffers, 2008;Grealish et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Student nurses encounter many challenging learning situations in nursing homes, but limited access to qualified supervision and support may prevent them from fully utilizing the learning potentials (Davies et al, 2002;Lees et al, 2006;Kerridge, 2008;Xiao et al, 2008). Negative experiences during clinical placements are considered one of the reasons why nursing students hesitate to engage in aged care, and efforts to enhance the learning environment during clinical placements in nursing homes, may positively affect nursing students' attitudes and their future choice of employment (Grealish et al, 2010;McKenna et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation